Peran Infrastruktur Teknologi dalam Mengakselerasi Ekosistem Kewirausahaan dan Produktivitas Ekonomi - Muhammad Irfan; Eddy Soeryanto Soegoto (Lembaga Pengembangan Kinerja Dosen, 2026)
This study analyzes the strategic role of technology infrastructure in accelerating entrepreneurship ecosystem maturity and its impact on national economic productivity. Addressing data distribution biases in the digital economy, the research employs rigorous Structural Equation Modeling (SEM) using World Bank WDI data. The model examines three constructs: the exogenous variable Technology Infrastructure (TECH) (measured by secure internet servers, fixed broadband, and high-tech exports); the mediating variable Entrepreneurship Ecosystem (ENT) (proxied by domestic credit and trademark applications); and the endogenous variable Economic Productivity (PROD) (evaluated via GDP per person employed, patents, and industry value added).To ensure multivariate normality and minimize outlier effects, the study applied Natural Logarithm (Ln) transformations to skewed variables. Analysis using Jamovi reveals that technology infrastructure is a critical foundation that significantly creates a conducive entrepreneurship ecosystem. Consequently, this strong ecosystem mediates technology’s impact, enhancing long-term economic productivity. The findings suggest that investment in digital infrastructure—particularly cybersecurity—and strict statistical validity are vital for policymakers to drive innovation-based growth and avoid the middle-income trap.